Analisis Faktor-Faktor yang Mempengaruhi Asset Misappropriation Berdasarkan Fraud Diamond Theory : Studi Kasus pada PT. XYZ - Indra Cahya Kusuma; Ayi Jamaludin Aziz (AKUNTANSI 45, 2025)
This study aims to analyze the factors that influence asset misappropriation based on the Fraud Diamond Theory, focusing on pressure, opportunity, rationalization, and capability as the main variables. The population in this study is the Quality Assurance Department in a manufacturing company. Sampling in this study uses a survey method. With a quantitative approach, the data of this study were obtained by distributing questionnaires to 50 respondents and processed using JASP 0.14.1.0 with multiple linear regression analysis to test the relationship between these factors and asset misappropriation. The results of the study indicate that pressure, opportunity and capability have a significant effect on asset misappropriation and rationalization has no effect on asset misappropriation.